International product fragmentation and the insertion of Latin America and the Caribbean in global production networks: Colombian case studies - Marcela Meléndez; Maria José Uribe (Inter-American Development Bank (IDB), 2012)
Understanding the drivers of international production fragmentation is an important issue for Latin American and Caribbean countries because participation in global production networks can help mitigate instability due to dependence on natural resources and can provide opportunities for further exports diversification and increased growth. This paper contributes to the literature on global value chains by analyzing two case studies that examine the experience of Colombian firms that have successfully penetrated international markets through participation in global production networks. The stories of these firms are contrasted within the framework of the global value chain literature. A series of policy implications are drafted as a result of this exercise.
hdl:11319/4264
Keywords: F14; F23; 330; Global Supply Chains; International Fragmentation of Production; Suppliers